Sex differences in early-life programming of the hypothalamic–pituitary–adrenal axis in humans suggest increased vulnerability in females: a systematic review - Carpenter, T.; Grecian, S. M.; Reynolds, R. M. (Journal of developmental origins of health and disease, 2017)
Fetal glucocorticoid overexposure is a key mechanism linking early development with later-life disease. In humans, low birth weight associates with increased fasting cortisol, hypothalamic–pituitary–adrenal (HPA) axis reactivity, and with cardiovascular risk and cognitive decline. As there are sex differences in these adult diseases, we hypothesized that there may be sex differences in programming of the HPA axis in response to prenatal stressors. We conducted a systematic review following Meta-Analysis of Observational Studies in Epidemiology and Preferred Reporting Items for Systematic Reviews and Meta-Analysis. We searched Embase, MEDLINE and Web of Science from inception to 31 October 2016. We included studies related to sex differences, prenatal exposures and HPA axis. We excluded studies investigating specific disease states. The 23 included studies investigated the consequences of low birth weight, preterm birth and maternal stressors of asthma, psychosocial stress and glucocorticoid medications on HPA axis outcomes of placental glucocorticoid biology and offspring HPA axis function in early life and later life. Female offspring exposed to stressors had increased HPA axis reactivity compared with males. Furthermore, the female placenta increased its permeability to maternal glucocorticoids following maternal stress with changes in the expression of 11β-hydroxysteroid dehydrogenase enzymes in response to maternal glucocorticoid exposure or asthma. Among males there was some evidence of altered diurnal cortisol secretion. We conclude that although there is some evidence of male vulnerability leading to altered diurnal cortisol secretion, the female HPA axis is more vulnerable to programming, particularly in terms of its reactivity; this suggests a mechanism underlying sex differences in later-life diseases.